Grain boundary decohesion as the mechanistic origin of hydrogen embrittlement in tungsten explored through an experimental-computational framework - Yilmaz, Halil; Ornek, Cem; Payam, Beste; Hallmann, Daniel (Elsevier Science Sa, 2026)
This study demonstrates that hydrogen embrittlement in tungsten is dominated by intergranular brittle fracture arising from hydrogen segregation to grain boundaries, rather than by lattice-based decohesion (HEDE) or localised plasticity (HELP). Through an integrated approach of electrochemical hydrogen charging, mechanical testing, and first-principles calculations, we show that hydrogen insertion into the tungsten lattice is thermodynamically unfavourable, whereas segregation to grain boundaries is exothermic and leads to deep trapping. Each trapped hydrogen atom reduces the grain boundary fracture energy by similar to 1 J/m(2), and high concentrations lead to spontaneous decohesion. Mean-field elasticity modelling indicates that low levels of hydrogen (up to 55 wppm) increase stiffness, while higher concentrations induce elastic softening and instability. Experimentally, hydrogen-charged samples show premature fracture and intergranular cracking, supporting a grain-boundary-controlled fracture mode. Although hydrogen diffusion is rapid in a defect-free lattice (similar to 10(-10) m(2)/s), it is strongly suppressed in the presence of microstructural traps (similar to 10(-27) m(2)/s), indicating that transport is governed by defect networks rather than bulk solubility. These findings establish a clear mechanistic pathway for hydrogen embrittlement in tungsten, highlighting grain boundary engineering as a critical design strategy for hydrogen-resilient nuclear materials.
Keywords: Dft; Hydrogen Embrittlement; Nuclear Material; Tungsten; Tensile Testing